Equity and Inclusion in Physical Education. - Stidder, Gary (Taylor and Francis, 2012)
An essential component of good practice in physical education is ensuring inclusivity for all pupils, regardless of need, ability or background. Now in a fully revised and updated new edition, Equity and Inclusion in Physical Education fully explores the theoretical and practical issues faced by physical education teachers today. The book amalgamates areas of critical debate within the world of physical education and is structured around the key topics of ability, special educational needs, gender, sexuality, social class, race and ethnicity. These issues are discussed in relation to principle.